Effect of a Discharge Planning Program on the Quality of Life in Women With Breast Cancer - Yasaman Tamri; Zohreh Parsa Yekta (Journal of Holistic Nursing and Midwifery)
Introduction: Women with Breast Cancer (BC) under chemotherapy are at risk of complications affecting their Quality of Life (QoL), which need specific discharge planning. Objective: This study aims to investigate the effect of a discharge planning program on the QoL of women with BC. Materials and Methods: This quasi-experimental study was conducted on 72 women with BC undergoing chemotherapy referred to oncology wards in Kermanshah, Iran. They were divided into groups of intervention (n=35) and control group (n=35) using the block randomization method. For the intervention group, the discharge planning program was implemented individually and in group at least 4 sessions, each for 30-45 minutes. Patients’ QoL in both groups was measured before, one month after, and three months after intervention using two questionnaires of European Organization for Research and Treatment of Cancer (QLQ C-30 and QLQ-BR23). The collected data were analyzed using ANOVA, chi-square test, t-test, and repeated measures ANOVA. The significance level was set at 0.05. Results: The mean age of participants was 47.71±10.4 years, and majority of them were in the second stage of BC. There was a significant difference in all functional scales of QoL in the intervention group over time from baseline to three months after discharge (P<0.05), except in sexual functioning (P=0.119) and sexual enjoyment (P=0.210). Conclusion: The discharge planning program has a positive effect on the Quality of Life of women with Brest Cancer.